Fabry disease: alfa-galactosidase A deficiency and enzyme replacement therapy - Warnock, David (Henry Stewart Talks, 2007)
Diagnosis of Fabry disease, Metabolic defect: GL-3 accumulation, Multi-systemic manifestations, Case examples, Kidney pathology in Fabry disease, Enzyme therapy, Dialysis and transplantation, Analogy to diabetic nephropathy